Second generation of the World Wide Web (WWW) and education - Juškevičienė, Anita (Lietuvos matematikos rinkinys, 2010)
Various technologies are useful for the integration in teaching/learning process: students are motivated to learn, teachers can visually presente material and easier to organize teamwork. The article discusses several second generation of the www technologies and analyze their use in class options depending on communication, collaboration, storage and information searching possibilities by using these technologies. All these technologies include not only specific but and general characteristics and which technology choose to use depends on personal needs.